PERAN LEARNING CURVE DALAM OPTIMALISASI WAKTU DAN BIAYA PERAKITAN TAMIYA - Muhammad Syahrul Romadhon; Daffa Maulana Asviara, Aji Dewa Abdullah, Virdan Yunior Ismail, Iskandar Zulkarnaen (Jurnal Ekonomi dan Bisnis, 2024)
Every industry has a learning process, both small, medium and even large industries always carry out learning actions or what is often known as learning action. The learning process in an industry takes place continuously. Learning curve marks a phenomenon that occurs when people do the same work repeatedly and increase productivity as a result of increasing experience. This research uses a case study approach involving Tamiya assemblers from various levels of experience. Data was collected through direct observation and recording assembly times for each Tamiya unit produced. that the Learning Curve not only helps optimize time and costs in Tamiya assembly, but also plays a role in increasing efficiency, reducing production costs, improving product quality, and encouraging innovation in the long term. With 10 trial times, the results were 5.8 seconds and the CAT graph experienced a drastic decrease, so it can be concluded that the Learning Curve can influence the time and cost of Tamiya optimization.